ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP SARANA DAN PRASARANA PASAR SUKUN KOTA MALANG - Oktavianus Oba; Galih Damar Pandulu; Pamela Dinar Rahma (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2022)
AbstractThe method for measuring the level of customer satisfaction in the traditional market of Sukun is the Importance and Performance Analysis method. The purpose of importance-performance analysis is to obtain information about the level of customer satisfaction with services through measuring the level of importance and the level of implementation. The level of importance of service quality is how important a service variable is for customersThe data needed is obtained through primary surveys with interviews with consumers to obtain customer perceptions of satisfaction and interest as well as secondary data in the form of Sukun market land area, number of traders and data on existing facilities.The results of the analysis show that the average value of performance is 3.16 and the average value of importance is 4.34. Furthermore, the average number of performances is used as a quadrant limiting point based on the X axis and the average value of interest is used as a quadrant limiting point based on the Y axis.Keywords: Satisfaction, Community, Facilities and Infrastructure, Sukun Market